Synaptophysin gene expression in schizophrenia. Investigation of synaptic pathology in the cerebral cortex. - Eastwood, S; Cairns, N; Harrison, P (2000)
BACKGROUND: Decreased expression of proteins such as synaptophysin in the hippocampus and prefrontal cortex in schizophrenia is suggestive of synaptic pathology. However, the overall profile of changes is unclear. AIMS: To investigate synaptophysin gene expression in the cerebral cortex in schizophrenia. METHOD: The dorsolateral prefrontal (Brodmann area [BA] 9/46), anterior cingulate (BA 24), superior temporal (BA 22) and occipital (BA 17) cortex were studied in two series of brains, totalling 19 cases and 19 controls. Synaptophysin was measured by immunoautoradiography and immunoblotting. Synaptophysin messenger RNA (mRNA) was measured using in situ hybridisation. RESULTS: Synaptophysin was unchanged in schizophrenia, except for a reduction in BA 17 of one brain series. Synaptophysin mRNA was decreased in BA 17, and in BA 22 in the women with schizophrenia. No alterations were seen in BA 9/46. CONCLUSIONS: Synaptophysin expression is decreased in some cortical areas in schizophrenia. The alterations affect the mRNA more than the protein, and have an unexpected regional distribution. The characteristics of the implied synaptic pathology remain to be determined.